2019
DOI: 10.1155/2019/3784172
|View full text |Cite|
|
Sign up to set email alerts
|

Expression Analysis of Fibronectin Type III Domain-Containing (FNDC) Genes in Inflammatory Bowel Disease and Colorectal Cancer

Abstract: Background. Fibronectin type III domain-containing (FNDC) proteins fulfill manifold functions in tissue development and regulation of cellular metabolism. FNDC4 was described as anti-inflammatory factor, upregulated in inflammatory bowel disease (IBD). FNDC signaling includes direct cell-cell interaction as well as release of bioactive peptides, like shown for FNDC4 or FNDC5. The G-protein-coupled receptor 116 (GPR116) was found as a putative FNDC4 receptor. We here aim to comprehensively analyze the mRNA expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…The FNDC1 gene is closely related to many diseases. Wuensch (20) found that FNDC1 was associated with pathological changes in inflammatory bowel disease. Van 21performed a WES study and found that FNDC1 plays an important role in the development of acute otitis media in children.…”
Section: Discussionmentioning
confidence: 99%
“…The FNDC1 gene is closely related to many diseases. Wuensch (20) found that FNDC1 was associated with pathological changes in inflammatory bowel disease. Van 21performed a WES study and found that FNDC1 plays an important role in the development of acute otitis media in children.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the overexpression of FNDC1 was found to be correlated with a poor prognosis in patients with gastric cancer (11). An upregulation of FNDC1 has also been revealed in head and neck squamous cell carcinoma and colorectal cancer (12,13). However, there have been few studies regarding the roles of FNDC1 in the progression of BC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that ADGRF5 and S1P 1 may Alvarez et al (2011) and Kahn (2014) function in concert to regulate the BBB (Yanagida et al, 2017). A recent report suggests ADGRF5 may also function as a receptor for fibronectin type III domain-containing proteins (FNDC;Wuensch et al, 2019). Several studies have identified ADGRA2, also known as GPR124, as a key endothelial regulator of brain-specific angiogenesis (Obermeier et al, 2013;Sweeney et al, 2019).…”
Section: Adhesion Familymentioning
confidence: 99%